The focusing effect of self-evaluation threat in coaction and social comparison. [article]. - Muller, Dominique
This article contends that the presence of a coactor leads to a focusing effect whenever this presence represents a threat or potential threat to self- evaluation. Experiment 1 showed that attentional focusing appears in the presence of an actual (in the case of upward comparison) or potential (in the case of mere coaction) threat to self-evaluation but not in its absence (in the case of downward comparison). Experiments 2 and 3 confirmed that the presence of a coactor effects focusing because the coactor represents a potential threat and showed that introducing a threat in downward comparison can produce a focusing effect. Experiment 4 showed that removing a threat in upward comparison decreases the focusing effect. Experiment 5 confirmed that the effects observed in upward comparison are due to attentional focusing and not to an increase in effort. Contributions to social facilitation, social comparison, and attention are discussed. -- (from the author)
Keywords: Social comparison; Self-evaluation threat; Coaction; Illusory conjunction; Attentional focusing